An efficient zero-laxity based real-time multiprocessor scheduling algorithm - Alhussian, H. (Institute of Electrical and Electronics Engineers Inc., 2015)
In this paper, we present an efficient global real- time multiprocessor scheduling algorithm based on the beneficial Zero-Laxity policy. The algorithm selects tasks for execution based on their execution requirements. Tasks with largest execution requirements are always scheduled first; however when a task reaches zero laxity it is given the highest priority and executed until completion. The simulation showed that the proposed algorithm misses few deadlines and achieves high schedulability levels compared to currently existing zero laxity based algorithms. Â© 2015 IEEE.